Impact of pre-treatments on Albizia procera and Albizia chinensis seed germination and early growth performance in Nursery, Mizoram, India - Musa, Faisal Ismail; Sahoo, Uttam Kumar (Forest science and technology, 2025)
Effective pre-treatments are essential for improving germination and seedling establishment in the tree species with hard seed coats, such as Albizia procera and Albizia chinensis. This study evaluated the effects of five pre-treatments viz. hot water, cold treatment, cow-dung, H 2 SO 4 , and gibberellic acid (GA 3 ) and compared these with a control (no pretreatment) on seed germination and early seedling growth performance of these two species in nursery, Mizoram, India. Hot water treatment achieved the highest germination percentage (75.83% for A. procera and 86.11% for A. chinensis), while H 2 SO 4 treatment had the shortest mean germination time (4.5 days for A. procera and 8.87 days for A. chinensis). Germination energy peaked in the first week for A. procera under H 2 SO 4 treatment (58.06%) while in the second week for A. chinensis with hot water treatment (63.38%). Seedlings showed superior growth performance in summer compared to winter, influenced by soil temperature. After one year, seedlings treated with hot water reached the highest heights 123.75 cm for A. chinensis and 125.72 cm for A. procera under cow dung. The Dickson's quality index (DQI) indicated good seedling quality for both species. Hot water is recommended as a simple, cost-effective method to enhance germination and produce vigorous seedlings, suitable for afforestation and restoration programs.